Islam dan Mediatisasi Agama - Aulia, Nisa Nur (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2017)
The media has become an important resource, the media provide information on issues of religion, religious information and experience to be formed in accordance with the demands of media genres that are popular. As the cultural and social environment, the media has taken over many of the functions of cultural and social aspects of the institutionalized religions and provide spiritual guidance, moral orientation, verses ritual and a sense of community and belonging. This paper discusses the relationship between mediatisation and secularization at three levels, namely: people, organizations and individuals. At the community level, mediatisation is an integral part of the secularization. At the level of organizations and individuals, mediatisation may well encourage the practice and beliefs of secular and religious imagination usually invite more subjective nature.